2006
DOI: 10.1007/s10705-006-9014-1
|View full text |Cite
|
Sign up to set email alerts
|

Lack of increased availability of root-derived C may explain the low N2O emission from low N-urine patches

Abstract: and CO 2 emissions from the monoliths as well as δ 13 C signal of evolved CO 2 were done on day -4, -1, 0, 1, 2, 4, 5, 6 and 7 after application of urine corresponding to 3.1 and 5.5 g N m -2 in the first and second experiment, respectively. The δ 13 C signal was also determined for soil organic matter, dissolved organic C and CO 2 evolved by microbial respiration. In addition, denitrifying enzyme activity (DEA) and nitrifying enzyme activity (NEA) were measured on day -1, 2 and 7 after the first urine applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
2
3
1
Order By: Relevance
“…In contrast to several studies, which showed that N 2 O emissions from urine and dung/faeces patches are mostly significantly increased (Lovell and Jarvis 1996;Mosier et al 1998;Yamulki et al 1998;Petersen et al 2004;Clough et al 2004;van Groeningen et al 2005;Ma et al 2006;Carter et al 2006), we failed to demonstrate a significant stimulating effect of urine and faeces additions on N 2 O emissions for steppe soils in Inner Mongolia. In the case of faeces dropped at steppe sites we hypothesise that the lack of a stimulating effect on N 2 O emissions was due to the quick drying of faeces after its exposure to the ''dry'' climatic conditions in the field.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to several studies, which showed that N 2 O emissions from urine and dung/faeces patches are mostly significantly increased (Lovell and Jarvis 1996;Mosier et al 1998;Yamulki et al 1998;Petersen et al 2004;Clough et al 2004;van Groeningen et al 2005;Ma et al 2006;Carter et al 2006), we failed to demonstrate a significant stimulating effect of urine and faeces additions on N 2 O emissions for steppe soils in Inner Mongolia. In the case of faeces dropped at steppe sites we hypothesise that the lack of a stimulating effect on N 2 O emissions was due to the quick drying of faeces after its exposure to the ''dry'' climatic conditions in the field.…”
Section: Discussioncontrasting
confidence: 99%
“…This would suggest that nitrification could have had a predominant role as a source of emissions in our experiments. Similar results were shown by (Bol et al, 2004, Carter et al, 2006) in a Danish pasture. Carter et al (2006) also attributed N 2 O emissions from nitrification after application of low N urine (0.7 g N l −1 ) to a sandy soil.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were shown by (Bol et al, 2004, Carter et al, 2006) in a Danish pasture. Carter et al (2006) also attributed N 2 O emissions from nitrification after application of low N urine (0.7 g N l −1 ) to a sandy soil. They claimed that, under high N urine, nitrification will be inhibited for few days, possibly due to root scorching.…”
Section: Discussionsupporting
confidence: 91%
“…Without plant-derived readily available C, soil N 2 O emissions have been reported to be low under urine patches (Carter et al 2006 Significance refers to the comparison between temperature/plant/urine treatments. ***p<0.001; **p<0.01; *p<0.05; ns (not significant) Table 4 Leaf and root dry weight biomass (g pot −1 ) and nitrogen updake (mg pot −1 ) at the end of the experiment (672 h following the urine treatment).…”
Section: N 2 O Fluxesmentioning
confidence: 99%